Zusammenhang von Herzfrequenzvariabilität (HRV) und subjektiv empfundener Gesamtbeanspruchung (sRPE) bei Spielsportlern - Megerle, F.; Reim, D.; Giewekemeyer, H.; Gerhard, J.; Hoos, O. (Herzfrequenzvariabilität: Gesundheitsförderung - Trainingssteuerung - Biofeedback. Internationales Symposium am 29. und 30. Oktober., 2011)
Recent studies suggest potential for heart rate variability (HRV) and the session rating of perceived exertion (sRPE) to monitor exercise load and training status. The major goal of this pilot-study was to evaluate the possible relation between perceived exertion (sRPE) and HRV as measures of training load during an eight-week training Programme performed by semi-professional teamsport players. n = 5 basketball players (25,4 ±2,2 a; 90,4 ± 12,1 kg) of a second division basketball team provided sRPE-values for each training session and HRV-measures MeanRR, RMSSD and SDNN (ms) in supine and upright position at the beginning (t0), after four weeks (t1) and after eight weeks (t2) of the training regime. Additionally, a Yo-Yo intermittent recovery test level 1 (YoYolR1) was used to assess game specific endurance capacity at t0 and t2. The results show that sRPE scores of 195 ± 28 in the first and 231 ± 22 in the last four weeks induced a 10% gain in YoYolR1-test. HRV-parameters after 4 weeks (t1) had fairly similar values compared to baseline (t0), while they tended to increase between t1 and t2 (0,05 < p < 0.10) resulting in MeanRR. RMSSD and SDNN-values of plus 11%, 36% and 20 % after 8 weeks of training. While no relation between sRPE and HRV could be found for the first four weeks, in the second training period this relation could be best described by an inverse U-shaped curve with highest HRV for medium sRPE. These results indicate a possible dose-response-relationship between perceived training load and HRV that should be enligthened in future studies with larger sample size.